Election of farmers in the adoption of soil management technologies in cotton production system and crop rotation in the warm Alto Magdalena valley (2012)
Agricultural research institutions have created technologies that aim to present alternative solutionsto the constraints of agricultural production through the generation of products and processes. However, in most cases, the adoption and impact of technology are unknown, presenting a constraint to the development of successful policies and technologies. This study analyzed the decision-making for soil management technologies generated by Corpoica in the warm valley region of the Alto Magdalena. A Logit model was formulated for determining the probability of adopting the technologies. This study illustrates that conventional tillage technologies, which contribute to a lower incidence of weeds, and the availability of machinery most likely explain increased adoption; in addition, the land is an important factor in explaining adoption, with an increased use of sustainable technologies when the farmer is the owner.